Geology, structural evolution and controls of hydrothermal gold mineralization in the Eastern Karagwe-Ankole fold belt, North Western Tanzania - Koegelenberg, Corne (Stellenbosch : Stellenbosch University, 2016)
Thesis (DSc)--Stellenbosch University, 2016.